Variable rate application of plant protection products (fungicides on winter wheat) - Ansell, Alex (Cranfield University, 2021)
Variable rate application (VRA) has the potential to allow farmers to use the most suitable dose rate of fungicides required for their winter wheat fields. Currently, the dominant practice is to apply fungicides at a uniform dose rate irrespective of in field variability. VRA could reduce fungicide costs, prevent chemical resistance, and reduce environmental damage. Whilst VRA is more commonplace in Nitrogen applications and more recently plant growth regulator (PGR) applications, there is still a hesitancy to use VRA for fungicide applications. With the removal of fungicide active ingredients and resistance to actives, the future of fungicide application is to determine the most appropriate dose and reducing over-spraying where possible. The primary aim of this thesis was to understand how to achieve VRA of fungicides on winter wheat, most effectively and efficiently in the future. To achieve this, several research gaps were investigated. Research was conducted into the ‘state of the art’ VRA technology finding that the main barriers are cost and perceived risk of inconsistency of effect. A laboratory trial was conducted in 2018 to study the deposition of a dye representative of fungicide through the winter wheat growing season. Destructive sampling was conducted to determine the variation in quantity of dose rate per gram of biomass for each fungicide application timing, finding the later growth stages received the greatest dose but the dose relative to the biomass was lower than earlier growth stages. In 2019, March – June, a field study was conducted over two farms to measure the spatial and temporal variation in volumetric biomass and determine if NDVI is a suitable basis for application decisions, finding that monitoring at T0 and T1 growth stages was best for reflecting canopy variability. From this, a new method was piloted to extract NDVI min and max values from 43,000 winter wheat fields in 2018. This was to understand the range of variation, in NDVI values at T1, in winter wheat fields is enough to continue investing in VRA. Finally, a cost benefit analysis was performed comparing a standard uniform dose and a VRA system, finding a saving of £13.82/ha on one farm from one VRA spray (T1). If a similar saving was made at T0, T2, and T3 an overall saving would be made of £55.28/ha. This study provides methodology for conducting VRA and a foundation for future VRA investigations.
Corstanje, Ronald - Associate Supervisor
Keywords: NDVI; Remote Sensing; Variability; cost; growth stages; application